2021
DOI: 10.48550/arxiv.2107.09182
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Incorporating domain knowledge into neural-guided search

Abstract: Many AutoML problems involve optimizing discrete objects under a black-box reward. Neural-guided search provides a flexible means of searching these combinatorial spaces using an autoregressive recurrent neural network. A major benefit of this approach is that builds up objects sequentially-this provides an opportunity to incorporate domain knowledge into the search by directly modifying the logits emitted during sampling. In this work, we formalize a framework for incorporating such in situ priors and constra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…However, in this work we show that respecting physical constraints actually helps improve SR performance not only in terms of interpretability but also in accuracy by guiding the exploration of the space of solutions towards exact analytical laws. This is consistent with the studies of Petersen et al (2019Petersen et al ( , 2021; Kammerer et al (2020) who found that using in situ constraints during analytical expression generation is much more efficient as it vastly reduces the search space of trial expressions (though we note their machinery is not capable of incorporating units constraints as it requires one to compute and exploit the whole graph describing an expression as a relational tree).…”
Section: Search Spacesupporting
confidence: 90%
See 2 more Smart Citations
“…However, in this work we show that respecting physical constraints actually helps improve SR performance not only in terms of interpretability but also in accuracy by guiding the exploration of the space of solutions towards exact analytical laws. This is consistent with the studies of Petersen et al (2019Petersen et al ( , 2021; Kammerer et al (2020) who found that using in situ constraints during analytical expression generation is much more efficient as it vastly reduces the search space of trial expressions (though we note their machinery is not capable of incorporating units constraints as it requires one to compute and exploit the whole graph describing an expression as a relational tree).…”
Section: Search Spacesupporting
confidence: 90%
“…units prior was hinted by Petersen et al (2021), to the best of our knowledge such a framework was never built before.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation